Sunday

December 21, 2014

December 21, 2014

Posted by **mema** on Thursday, June 9, 2011 at 9:07pm.

- algebra -
**PsyDAG**, Friday, June 10, 2011 at 3:34pm9x^2-36x+36 = 9

9x^2-36x+27 = 0

Factor. Get two factors from each of the end terms that will add to the value of the middle term.

(3x-9)(3x-3) = 0

Set each factor = 0 and solve.

**Answer this Question**

**Related Questions**

intermediate algebra - given the quadratic function f(x)=9x^2+36x+36, finda ...

algebra - given the quadratic function f(x) 4x^2 -24x +36 find the value of x ...

math - Given the quadratic function f(x) = x2 – 12x + 36, find a value of x such...

math - Given the quadratic function f(x) = x2 – 18x + 81, find a value of x such...

Algebra - Can you please help me with the following problems? Find the ...

math - Given the quadratic function f(x) = 16x^2 – 64x + 64, find a value of x ...

math - Given the quadratic function f(x) = 16x2 – 64x + 64, find a value of x ...

math - Given the quadratic function f(x) = 16x2 – 64x + 64, find a value of x ...

Algebra Problems - Please check my answers. Find the coordinates of the vertex ...

Algebra Help - Determine without graphing, whether the given quadratic function ...